2015
DOI: 10.1021/acscatal.5b01737
|View full text |Cite
|
Sign up to set email alerts
|

Nanostructured Electrocatalysts for PEM Fuel Cells and Redox Flow Batteries: A Selected Review

Abstract: PEM fuel cells and redox flow batteries are two very similar technologies which share common component materials and device design. Electrocatalysts are the key components in these two devices. In this Review, we discuss recent progress of electrocatalytic materials for these two technologies with a focus on our research activities at Pacific Northwest National Laboratory (PNNL) in the past years. This includes (1) nondestructive functionalization of graphitic carbon as Pt support to improve its electrocatalyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(35 citation statements)
references
References 125 publications
0
35
0
Order By: Relevance
“…We can calculate the potential difference, E,f rom Equation (5). We can calculate the potential difference, E,f rom Equation (5).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We can calculate the potential difference, E,f rom Equation (5). We can calculate the potential difference, E,f rom Equation (5).…”
Section: Resultsmentioning
confidence: 99%
“…In recent years, environmental pollutiona nd energy issues caused by the consumption and depletion of fossil fuels have increasingly hindered the coordinated development of the economy ands ociety.T hus, much effort has been made to seek some practical solutions, including solar cells, [1] lithiumion batteries, [2] rechargeable metal-air batteries or metaloxygen batteries, [3,4] and fuel cells. [5,6] As an advanced energy storaged evice, the rechargeable hybrid LiÀO 2 battery hasa ttracted great attention owing to its high theoretical specific energy (5200 Wh kg À1 ,w hich is much highert han that of the lithium-ion battery), [7,8] low cost, and environmental friendliness. Although the rechargeable hybrid LiÀO 2 battery is attractive, somep roblems still severely limit its popularization in practice, [9][10][11][12] such as the inherently sluggishk inetics of the oxygen reduction reaction (ORR) and oxygen evolution reaction (OER) on the surfaceo ft he anode.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, introducing an ideal support with well‐designed nanostructures has been emerging as a novel approach to enhance performance of metallic electrocatalyst . For instance, Wu and co‐workers reported that N‐doped hollow porous carbons derived from metal–organic frameworks (MOFs) can be used as promising support for electrocatalyst, which revealed good affinity to the surface of metallic nanoparticles (NPs) .…”
Section: Introductionmentioning
confidence: 99%
“…In this review, we focus on catalysts used with phosphoric acid and HT-PEMFC systems with the goal of reducing catalyst cost and improving activity for the ORR. For more detail, [95][96][97][98][99] provides a more complete review of catalysts used in polymer electrolyte fuel cell systems.…”
Section: Orr Catalyst Activity In Free Electrolyte: Alternative Catalystmentioning
confidence: 99%